2011
DOI: 10.1017/s1461145711000587
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin at the level of the amygdala and orbitofrontal cortex modulates distinct aspects of positive emotion in primates

Abstract: Impaired top-down regulation of the amygdala, and its modulation by serotonin (5-HT), is strongly implicated in the dysregulation of negative emotion that characterizes a number of affective disorders. However, the contribution of these mechanisms to the regulation of positive emotion is not well understood. This study investigated the role of 5-HT within the amygdala and the orbitofrontal cortex (OFC), on the expression of appetitive Pavlovian conditioned emotional responses and their reversal in a primate, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 73 publications
2
10
0
Order By: Relevance
“…Anatomical studies in rhesus monkeys and macaques have revealed that innervation of the medial orbitofrontal cortex arises specifically from the DRI region, that is, in the caudal part of the dorsal raphe nucleus, between the medial longitudinal fasciculi (Porrino and Goldman-Rakic, 1982 ; Cavada et al, 2000 ). Together with emerging evidence that serotonin functions in the orbitofrontal cortex to either facilitate exploitation of current resources or exploration of alternatives based on reward expectations (Roberts, 2011 ), and to coordinate positive affective responses (Man et al, 2012 ), these findings are consistent with a potential role of DRI serotonergic neurons projecting to the medial orbitofrontal cortex in positive affective responses to warm temperature. DRI neurons also appear to innervate the ventral striatum (Van Bockstaele et al, 1993 ) and anterior cingulate cortex (Porrino and Goldman-Rakic, 1982 ), regions that, together with the medial orbitofrontal cortex, show correlations with subjective pleasantness ratings made to warm and cold stimuli (Rolls et al, 2008 ).…”
Section: Brain-body Circuitry Linking Non-noxious Thermosensation To supporting
confidence: 64%
“…Anatomical studies in rhesus monkeys and macaques have revealed that innervation of the medial orbitofrontal cortex arises specifically from the DRI region, that is, in the caudal part of the dorsal raphe nucleus, between the medial longitudinal fasciculi (Porrino and Goldman-Rakic, 1982 ; Cavada et al, 2000 ). Together with emerging evidence that serotonin functions in the orbitofrontal cortex to either facilitate exploitation of current resources or exploration of alternatives based on reward expectations (Roberts, 2011 ), and to coordinate positive affective responses (Man et al, 2012 ), these findings are consistent with a potential role of DRI serotonergic neurons projecting to the medial orbitofrontal cortex in positive affective responses to warm temperature. DRI neurons also appear to innervate the ventral striatum (Van Bockstaele et al, 1993 ) and anterior cingulate cortex (Porrino and Goldman-Rakic, 1982 ), regions that, together with the medial orbitofrontal cortex, show correlations with subjective pleasantness ratings made to warm and cold stimuli (Rolls et al, 2008 ).…”
Section: Brain-body Circuitry Linking Non-noxious Thermosensation To supporting
confidence: 64%
“…Electrophysiological studies have shown that 5-HT inhibits pyramidal cell firing in the OFC (Rueter et al, 2000;Wallace et al, 2014). The depletion of brain 5-HT or chronic intermittent stress, which reduces frontal cortex 5-HT release, impairs the ability of animals to adapt their response to changes in reward contingencies in the environment, resulting in perseverative behaviour (Bondi et al, 2008;Clarke et al, 2007;Man et al, 2012). Furthermore, increasing serotonergic tone with acute or chronic SSRI treatments has been reported to enhance cognitive flexibility and to decrease perseverative behaviours (Bari et al, 2010;Furr et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a recent study by Man and colleagues (2011), serotonergic lesions of the primate amygdala received late in life failed to disrupt appetitive Pavlovian learning but did retard the ability to generate changes in heart rate. Similar findings were also found in animals of the current study.…”
Section: Discussionmentioning
confidence: 99%